INFLUENCES OF TRANSCENDENTAL LEADERSHIP ON POTENTIAL DEVELOPMENT IN PRIVATE COLLEGES AND UNIVERSITIES IN SHENYANG CITY UNDER LIAONING PROVINCE - Bo, Zhang; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of research were: (1) To explore the components of potential development in private colleges and universities in Shenyang city under Liaoning Province; (2) To investigate the transcendental leadership affecting potential development in private colleges and universities in Shenyang city under Liaoning Province;(3) To develop guidelines for improving transcendental leadership in private colleges and universities in Shenyang city under Liaoning Province. This research methodology was a mixed-methods, including both quantitative and qualitative research. A stratified sampling method was used to collect data 356 from 3842 individuals who came from 6 outstanding private colleges and universities in Shenyang city under Liaoning Province. The population of the research consisted, lecturers from the 6 schools The sample size was determined by Krejcie and Morgan’s Table (1970). The key informants consisted of 10 key informants who obtained by purposive sampling method, they have the rich management and teaching experience. The instruments used for data collection were In-Depth interview,5-Points Likert Scale and Focus group discussion. Statistical method was used data analysis, including Exploratory Factor Analysis (EFA)and Multiple Regression Analysis. The results finding reveal that: (1) There were 5 components of potential development in private colleges and universities in Shenyang city under Liaoning Province which consisted of education and talent development; business and discipline benefits; financial resources; human resources and discipline team building, and innovation and scientific research. (2) There were total 30 managerial guidelines of potential development of private colleges and universities in Shenyang city under Liaoning Province which consisted of 6 managerial guidelines for component of education and talent development; 6 managerial guidelines for component of business and discipline benefits; 6 managerial guidelines for component of financial resources; 6 managerial guidelines for component of human resources and discipline, and 6 managerial guidelines for component of innovation and scientific research.